2023
DOI: 10.1002/mnfr.202200531
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inulin‐Type Fructans on Plasma Trimethylamine N‐Oxide Levels in Peritoneal Dialysis Patients: A Randomized Crossover Trial

Abstract: Scope: Trimethylamine N-oxide (TMAO), an important proatherogenic uremic toxin, is oxidized by hepatic-flavin monooxygenases from gut microbiome-generated trimethylamine (TMA). The present study aims to explore whether manipulating the gut microbiota by inulin-type fructans (ITFs) can reduce circulating TMAO levels in peritoneal dialysis patients. Methods and results: This is a randomized, double-blind, placebo-controlled, crossover trial with 10 g day −1 ITFs intervention for 3 months in continuous ambulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, in another study, intervention with inulin-type fructans (10 g/day) for 3 months altered composition of gut microbiome, but did not reduce the plasma TMAO level in patients undergoing peritoneal dialysis ( 130 ). This observation may be related to the duration and dose of the intervention.…”
Section: Role Of Inulin In Diseasementioning
confidence: 99%
“…However, in another study, intervention with inulin-type fructans (10 g/day) for 3 months altered composition of gut microbiome, but did not reduce the plasma TMAO level in patients undergoing peritoneal dialysis ( 130 ). This observation may be related to the duration and dose of the intervention.…”
Section: Role Of Inulin In Diseasementioning
confidence: 99%
“…Moreover, a study using 21 g/day of unripe banana flowers for 4 weeks decreased the indoxyl sulfate (IS) in patients undergoing PD [93]. Although the previous studies demonstrate that the supplementation changed the gut microbiota and affected the plasma levels of some uremic toxins in PD, [94] demonstrated that 10 g/day of inulin was not sufficient to decrease the TMAO serum levels, another uremic toxin associated with inflammation and CVD in patients with CKD undergoing dialysis [94]. The use of prebiotic fiber needs more studies, but so far, promising results in mitigating factors related to inflammation have already been demonstrated.…”
Section: Prebiotic Probiotic and Symbioticmentioning
confidence: 99%
“…143 Xiong et al found that ITFs increased the Firmicutes/Bacteroidetes (F/B) ratio and improved the gut microbial composition in peritoneal dialysis patients. 144 B. infant and human milk oligosaccharides (HMOs) comprised a synbiotic that increased the level of butyric acid in the adult gut and inhibited other harmful bacteria, thus maintaining the gut homeostasis. 65 Makki et al found that oligofructose increased the abundance of 6α-hydroxybile acid-associated bacteria and suggested that the pairing of oligofructose with 6α-hydroxybile acid-producing bacteria could be a new therapeutic option for patients with type II diabetes.…”
Section: Upgrading Of “Bacteria–drug Combination”mentioning
confidence: 99%